Power line carrier technology and home automation - Ishak N.; Din N.Md.; Jamaludin M.Z.; Thayoob Y.H.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electrical power network is a very large infrastructure which covers almost all part of the places in the world. With its widely spread network and connectivity, electrical power network infrastructure can be utilized as a communication medium. Promisingly, power line carrier communication can become an inexpensive, easy to install and high speed communication medium. Power line carrier technology refers to the process of sending and receiving data by using the existing electrical wiring. Power line carrier technology offers an inexpensive and easy to install communication access technology which will cover a very large area of network. This paper presents the challenges in implementing a power line carrier technology application. A practical implementation focusing on controlling home appliances is discussed. It is hoped that this research will give an overview of power line carrier technology and will contribute to its emergence in Malaysia. 2002 IEEE.